2013
DOI: 10.1073/pnas.1307154110
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative basis for neuroimaging of cortical laminae with calibrated functional MRI

Abstract: Layer-specific neurophysiologic, hemodynamic, and metabolic measurements are needed to interpret high-resolution functional magnetic resonance imaging (fMRI) data in the cerebral cortex. We examined how neurovascular and neurometabolic couplings vary vertically in the rat's somatosensory cortex. During sensory stimulation we measured dynamic layer-specific responses of local field potential (LFP) and multiunit activity (MUA) as well as blood oxygenation level-dependent (BOLD) signal and cerebral blood volume (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
97
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 63 publications
(110 reference statements)
9
97
2
Order By: Relevance
“…accumulation in the primary somatosensory cortex following stimulation reflect neuronal activity. Herman et al (2013) also showed that the somatosensory cortex responses acquired with various modalities were well correlated between layers (high Pearson's r score) and in particular middle and lower segments had similar responses with MUA as indicated by a slope of 1. In the present study, T 1 values between segments after the TGN stimulation stage were also well correlated in the range 0.2-1 s with slopes close to 1.0 for all the layers (not shown).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…accumulation in the primary somatosensory cortex following stimulation reflect neuronal activity. Herman et al (2013) also showed that the somatosensory cortex responses acquired with various modalities were well correlated between layers (high Pearson's r score) and in particular middle and lower segments had similar responses with MUA as indicated by a slope of 1. In the present study, T 1 values between segments after the TGN stimulation stage were also well correlated in the range 0.2-1 s with slopes close to 1.0 for all the layers (not shown).…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, we were able to detect cortical cytoarchitecture during a functional paradigm extending the potential of AIM-MRI. In their study, Herman et al (2013) showed a decrease of BOLD and cerebral blood volume responses in the rat somatosensory cortex from upper superficial to deep layers. On the other hand, multi-unit spike activity (MUA) and cerebral metabolic rate of oxygen (CMRO 2 ) increased.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations